An analysis of metaphors in the biographies of the 'GDR children of Namibia'. Issue 2 (2nd April 2020) - Müller, Karin; Niekrenz, Yvonne; Schmitt, Caroline; Krishnamurthy, Sarala; Witte, Matthias D.
ABSTRACT: Metaphors are linguistically dense images that transfer terms from their original usage to a different context and describe actions and objects beyond their literal meaning. This article uses Rudolf Schmitt's metaphor analysis (2017) to gain insight into the experiences of the so-called GDR children of Namibia. This term refers to a group of approximately 430 people who, as part of a solidarity project between the South West Africa People's Organisation (SWAPO) and the German Democratic Republic (GDR), were brought to the GDR between 1979 and 1989 to be trained as the elite for a future liberated Namibia. They grew up and attended school in the GDR until they were returned to Namibia in August 1990. Based on narrative interviews, we use metaphor analysis to show how the now-adult 'GDR children' experienced their lives between different national contexts. The interviewees talk about their collective education, feelings of heteronomy and the family bond that existed among the children themselves and between the children and their care staff. The metaphors they use underline the uniqueness of their upbringing.